Transparent microcrystalline glass and preparation method thereof

By controlling the crystal phase ratio of microcrystalline glass and introducing refractive index regulators, the problems of high haze and insufficient optical clarity of microcrystalline glass are solved, and high-strength and high-transparency microcrystalline glass is achieved, which is suitable for high-end display devices.

CN120817731APending Publication Date: 2025-10-21深圳市昊迦科技有限公司
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511191581.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-25
Publication Date
2025-10-21

AI Technical Summary

Technical Problem

While existing microcrystalline glass maintains high mechanical strength, it has problems such as high haze and insufficient optical clarity, making it difficult to meet the requirements of high-end display devices.

Method used

By controlling the ratio of the main crystalline phase, secondary crystalline phase and residual glass phase in transparent microcrystalline glass, combining P2O5/ZrO2 composite nucleating agent and graded heat treatment, limiting the grain size, and introducing refractive index regulators such as La2O3, CeO2, Nb2O5, TiO2, HfO2, and BaO, the refractive index difference between the glass phase and the crystal phase is optimized and light scattering is reduced.

Benefits of technology

The haze is reduced to below 0.1%, the transmittance reaches more than 89%, and high mechanical strength and optical clarity are maintained. It is suitable for mass production and chemical strengthening, and solves the application challenges of microcrystalline glass in high-end display devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120817731A_ABST
    Figure CN120817731A_ABST
Patent Text Reader

Abstract

The invention provides transparent microcrystalline glass and a preparation method thereof, and belongs to the technical field of glass preparation. The transparent microcrystalline glass comprises a primary crystal phase, a secondary crystal phase and a residual glass phase, the primary crystal phase comprises sodium nepheline and eucryptite, and the secondary crystal phase comprises at least one of zirconium oxide and beta quartz solid solution; the total crystallinity R is 40-75 wt%; the refractive index improvement coefficient k satisfies 0.05 < = k < = 0.20. The crystal phase proportion of the crystal phase and the glass phase is limited, so that the average grain size (less than or equal to 50 nm) is controlled, and the light scattering performance is reduced; by introducing a refractive index regulator and providing a refractive index improvement coefficient (k is more than or equal to 0.05 and less than or equal to 0.2), the refractive index difference between a crystal phase and a glass phase is reduced, and the problem of poor optical performance of the microcrystalline glass is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of glass manufacturing and provides a transparent microcrystalline glass and a preparation method and application thereof. Background Art

[0002] With the booming market for smart touchscreen electronics, consumers are increasingly demanding performance from device display cover panels, particularly higher drop resistance and superior scratch resistance. Against this backdrop, glass-ceramic, with its superior overall performance, is becoming the preferred cover material for consumer electronic devices and automotive displays.

[0003] Glass-ceramic is a high-performance ceramic material produced through precisely controlled nucleation and crystallization of a base glass. Essentially, it involves the introduction of uniformly distributed microcrystals into a glass matrix through heat treatment. These microcrystals act as reinforcements, significantly improving the material's mechanical strength (such as flexural strength and hardness) and chemical stability while maintaining excellent optical transparency. This high mechanical strength effectively protects against accidental drops and shocks, and it offers excellent scratch resistance. However, as consumer demands increase, so too do the demands placed on electronic glass products.

[0004] Currently, commercially available transparent glass-ceramics primarily utilize lithium disilicate or petalite as their primary crystalline phases. Meanwhile, new glass-ceramics systems with forsterite, magnesium aluminum zinc spinel, sodium pyroxene, and eucryptite as their primary crystalline phases are under active research and development, aiming to achieve even higher mechanical properties. However, electronic devices or displays place higher demands on the optical properties of the glass-ceramics used therein. Optical properties refer to the properties exhibited by a material when it absorbs, reflects, and refracts light, such as haze and |B| values. However, currently available glass-ceramics suffer from issues such as high haze, making them difficult to apply to display devices or electronic devices requiring high optical performance.

[0005] Glass-ceramics are composed of two phases, a crystalline phase and a glass phase, which typically have a significant difference in refractive index (the glass phase generally has a lower refractive index, while the crystalline phase has a higher refractive index). When incident light passes through the material, it is repeatedly refracted and scattered at the numerous crystal / glass interfaces. This is especially true when there are multiple primary crystalline phases, distinct crystalline systems, and significantly different proportions of each phase. The light scattering effect caused by these multi-phase interfaces with high refractive index differences can be dramatically enhanced, directly resulting in a decrease in the overall optical performance of the glass-ceramics.

[0006] Glass-ceramics containing multiple crystals generally have good mechanical properties. However, due to the different refractive indices of the crystals, visible light is scattered multiple times, resulting in poor haze. Poor haze can easily lead to poor imaging performance, making it difficult to meet the requirements of electronic glass. Existing heat treatment of glass-ceramics increases the scattering of incident light due to the presence of crystals, resulting in excessive haze. This problem is difficult to control during the glass-ceramics production process, and high haze is often used to achieve better mechanical properties. In the LAS system (lithium aluminum silicate (Li2O-Al2O3-SiO2) system), the presence of lithium disilicate and petalite makes it difficult to control the haze below 0.2%, and the field temperature uniformity requirements are high. During the heat treatment process, cracking, uneven haze, or uneven color coordinate B values ​​are likely to occur, resulting in low yield. As for the lower-cost NAS (sodium aluminum silicate (Na2O-Al2O3-SiO2) system) and LAS system, there are two different systems of crystals and glass phases in the microcrystalline glass, and obtaining easy-to-produce ultra-low haze microcrystalline glass faces great challenges.

[0007] To address this challenge, existing technologies provide some research and development technologies. For example, patent CN115893851A prepares microcrystalline glass with improved transmittance through specific heat treatment and chemical strengthening methods. However, the haze of the prepared microcrystalline glass is still relatively high and the consistency is poor. The reason is that due to the large difference in refractive index between the glass phase and the crystal phase, the visible light is scattered more after multiple deflections, resulting in a high haze of the microcrystalline glass. Patent CN120271235A also mentions that the microcrystalline glass currently on the market has problems such as high haze, but it is difficult to apply to display devices or electronic devices with high optical performance requirements.

[0008] Therefore, how to maintain the excellent mechanical properties of microcrystalline glass (especially high drop resistance and scratch resistance) while effectively reducing its haze and improving optical clarity has become a key technical challenge in promoting the wider application of this material in the field of high-end display cover panels. Summary of the Invention

[0009] In response to the issues raised in the aforementioned background technology, the primary objective of the present invention is to provide a transparent glass-ceramic, its preparation method, and its application. This invention aims to address the problem of high haze in polycrystalline, high-strength glass-ceramics due to severe light scattering and the interface differences between the crystalline and amorphous phases. The present invention strives to reduce haze and improve optical clarity while maintaining the high strength of the glass-ceramic.

[0010] In a first aspect, the present invention provides a transparent glass-ceramic, wherein the transparent glass-ceramic comprises a primary crystalline phase, a secondary crystalline phase, and a residual glass phase; The main crystalline phase includes sodium cryptite and eucryptite, The secondary crystalline phase includes at least one of zirconium oxide and beta quartz solid solution; The total crystallinity R is 40wt%-75wt%, In the transparent glass-ceramics, the residual glass phase accounts for M, the sodium nephrite accounts for N, and the eucryptite accounts for L, calculated by mass percentage. The following relationship must be satisfied among M, L, and N in the glass-ceramics: 1) 1.520≤(M×1.51+N×1.54+L×1.60)≤1.550; 2) 2.35≤N / L≤19.0.

[0011] In some embodiments, the total crystallinity R of the transparent microcrystalline glass is 50wt%-65wt%, preferably 50wt%, 52wt%, 54wt%, 56wt%, 58wt%, 60wt%, 62wt%, 64wt%, 65wt% and any one component in the range composed of any two of the above values.

[0012] In some embodiments, the N / L value is 4-17, preferably 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, and any two of the above values ​​constitute any component in the range.

[0013] In some embodiments, the average grain size of the transparent glass-ceramics is ≤50 nm, and the haze value of the glass-ceramics is denoted as H, H≤0.10.

[0014] In some embodiments, when the thickness of the microcrystalline glass is ≤2.0 mm, the transmittance is recorded as Tr, and at a visible light wavelength of 550 nm, Tr is ≥89%.

[0015] In some embodiments, the chemical components of the transparent microcrystalline glass, by mass percentage, include: SiO2: 40-62%, Al2O3: 15-26%, Na2O: 8-16%, K2O: 0.1-3%, Li2O: 2-10%, B2O3: 0.5-6%, P2O5: 2.5%-6.0%, ZrO2: 0.5-3.0%, Y2O3: 0.1-3% and clarifier: 0.1-1%.

[0016] Microstructure control mechanism: (1) Grain size constraint: The P2O5 / ZrO2 composite nucleating agent induces uniform nucleation, and combined with the graded heat treatment process, the average grain size is controlled to ≤50nm (much smaller than the visible light wavelength of 550nm), significantly reducing the Rayleigh scattering intensity.

[0017] (2) Grain boundary purification: B2O3 inhibits the separation of the glass phase at the grain boundary, Al2O3 enhances the bonding strength of the crystal phase / glass phase interface, and reduces the interface defect scattering center. The grain boundary environment of LAS and NAS composite crystal phases is more complex, and the scattering can be significantly reduced by refractive index matching and defect elimination.

[0018] In some embodiments, in order to ensure that the transparent glass-ceramics has better optical properties, a refractive index regulator or a clarifier is added to the glass-ceramics of the present invention and the refractive index regulator or the clarifier is quantified.

[0019] In some embodiments, the glass-ceramics further includes a refractive index adjuster by mass percentage.

[0020] In some embodiments, the refractive index modifier is at least one of La2O3, CeO2, Nb2O5, TiO2, HfO2, and BaO.

[0021] In some embodiments, the microcrystalline glass also includes a refractive index adjuster, which is selected from at least one of the following components by mass percentage: La2O3: 0-10%, CeO2: 0-3%, Nb2O5: 0-3%, TiO2: 0-5%, HfO2: 0-5%, BaO: 1-8%.

[0022] In some embodiments, in the glass-ceramics, the refractive index improvement coefficient k of La2O3, CeO2, Nb2O5, TiO2, HfO2, and BaO in the glass phase satisfies: k=(0.015×[La2O3]+0.02×[CeO2]+0.012×[Nb2O5]+0.02×[TiO2]+0.012×[HfO2]+0.012×[BaO]), satisfying 0.05≤k≤0.20.

[0023] Select high polarizability ions (such as La 3+ 、Ti 4+ ) to selectively increase the refractive index of the glass phase so that the maximum refractive index difference between the residual glass phase and the crystal phase at a wavelength of 587.6nm is |Δn|≤0.04, and the color coordinate b value range of the microcrystalline glass color control is: |b|≤1.5, eliminating the scattering loss caused by Fresnel reflection at the phase interface.

[0024] Refractive index control mechanism: introduction of high field strength ions (La 3+ 、Ti 4+) increases the electron density of the glass phase, achieving a refractive index increment dk / dC of up to 0.012-0.015 (C is the concentration of the refractive index modifier). The refractive index improvement factor k constraint (0.05≤k≤0.2) ensures the difference between the glass phase refractive index and the crystal phase, |Δn|, is ≤0.04, significantly reducing the total reflectance at the interface.

[0025] The present invention increases the refractive index of the glass phase by adding a refractive index modifier, thereby preventing incident light from being scattered by multiple large-angle refractions between two phases with high refractive index differences. Combining the optical advantages of the nanoparticles described above, the present invention reduces scattering and increases the refractive index.

[0026] In some embodiments, the clarifier is at least one of SnO2, SnO, NaCl, and Na2SO4.

[0027] In some embodiments, the glass-ceramics further includes a clarifier, and the clarifier is selected from at least one of the following components by mass percentage: SnO2: 0-1.0%, SnO: 0-1.0%, NaCl: 0-1.0%, and Na2SO4: 0-1.0%.

[0028] Furthermore, the clarifier accounts for 0.10-1.0% in the glass-ceramics.

[0029] In some embodiments, the transparent glass-ceramics has multiple crystal phases, and preferably does not contain a β-quartz solid solution phase.

[0030] In some embodiments, the microcrystalline glass of the present invention introduces a refractive index matching equation (i.e., the relationship that must be satisfied between M, L, and N in the microcrystalline glass) and a refractive index improvement coefficient during the design of the prescription.

[0031] The transparent glass-ceramic described in this invention features twinned sodalite and eucryptite. Eucryptite has a high refractive index, negative thermal expansion coefficient, and high elastic modulus, strengthening the glass-ceramic. Sodalite lowers the melting temperature, regulates the thermal expansion coefficient, promotes crystallization, and enhances mechanical strength. The primary crystalline phase consists of sodalite (refractive index N1≈1.54) and eucryptite (refractive index N2≈1.60), while the secondary crystalline phase is a solid solution of zirconium oxide or beta-quartz (refractive index≈1.51). By constraining the crystalline phase ratio and introducing a refractive index modification factor, the refractive index of the glass phase (n_g≈1.54) is controlled to approach that of the twinned phase. Simultaneously, the N / L ratio is limited to prevent localized crystal aggregation, thereby reducing light scattering at the phase interface.

[0032] In the second aspect, the present invention provides a method for preparing transparent microcrystalline glass, comprising the following steps: S1. uniformly mixing the chemical components and melting them at a temperature of 1450-1650° C. to obtain a glass melt; S2, clarifying and homogenizing the molten liquid at a temperature of 1450-1550° C., and obtaining a base glass after forming and annealing; S3. Heat-treating the base glass to obtain the transparent glass-ceramics.

[0033] In some embodiments, the chemical components have the definitions described above.

[0034] In some embodiments, the forming method includes one of a float method, a rolling method, an overflow down-draw method, and a continuous melting casting method.

[0035] In some embodiments, the base glass is heat-treated as follows: first, the temperature is raised to a nucleation temperature of 500-550°C and held for 1-5 hours, then the temperature is raised to 600-800°C for crystallization and held for 1-3 hours. Through the graded heat treatment process, a micro-ceramic glass with uniform grain size can be obtained.

[0036] In some embodiments, the transparent glass-ceramics or base glass is chemically strengthened to obtain chemically strengthened glass-ceramics. The resulting strengthened glass-ceramics has a Young's modulus ≥ 85 GPa, a drop ball impact energy ≥ 0.5 J, and a drop resistance on 120-grit sandpaper of not less than 1500 mm when the thickness is 0.6 mm.

[0037] In some embodiments, the chemical strengthening process is selected from one of the following methods: (1) the transparent glass-ceramics or base glass is subjected to ion exchange by immersing in a salt bath of molten sodium salt (such as NaNO3) at a temperature of about 350-480°C for about 1-36 hours, preferably in the temperature range of 400-480°C, and preferably in the time range of 2-15 hours. (2) the base glass or glass-ceramics is subjected to ion exchange by immersing in a mixed salt bath of molten potassium salt (such as KNO3) and sodium salt (such as NaNO3) at a temperature of about 360-480°C for 0.5-36 hours, preferably in the time range of 0.5-24 hours.

[0038] In a third aspect, the present invention provides an application of the transparent microcrystalline glass described in the present invention or the transparent microcrystalline glass prepared by the method described in the present invention as a protective cover material for electronic consumer products or a protective cover material for vehicle-mounted display devices.

[0039] Beneficial effects (1) The present invention limits the crystalline phase ratio of the main crystalline phase and the glass phase in the transparent microcrystalline glass of the LAS and NAS microcrystalline glass composite system to control the average grain size (≤50 nm), limit the N / L ratio to avoid local crystal phase aggregation, reduce light scattering, and improve optical properties (such as transparency, haze (≤0.1%), etc.).

[0040] (2) By introducing a refractive index modifier and proposing a refractive index improvement coefficient (satisfying 0.05≤k≤0.2), the present invention reduces the refractive index difference between the crystalline phase (primary crystalline phase and secondary crystalline phase) and the glass phase, narrowing the gap between the refractive index of the glass phase and the refractive index of the twin crystalline phase, thereby reducing light scattering at the phase interface and overcoming the problem of poor optical properties of LAS and NAS glass-ceramics composite systems. The technical solution of the present invention can achieve excellent optical properties while avoiding the loss of mechanical properties.

[0041] (3) The solution provided in the present application is suitable for mass production of large-sized transparent microcrystalline glass, is suitable for mass production, has a simple production process, and is easy to optimize and adjust. It overcomes the problems of cracking of whole bricks during heat treatment, uneven blocks, large differences in haze and color coordinate B values ​​that are very likely to occur in the mass production of large-sized microcrystalline glass, and obtains high-strength microcrystalline glass and chemically strengthened microcrystalline glass. The chemical strengthening conditions of the preparation method are easy to control, so that the prepared chemically strengthened microcrystalline glass has stable performance, high production efficiency, and low cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 This is a diagram of the microcrystalline glass according to Example 1 of the present invention.

[0043] Figure 2 This is a diagram of the microcrystalline glass of comparative example 3 of the present invention.

[0044] Figure 3 This is an X-ray diffraction overlay of Example 1 and Example 2 of the present invention.

[0045] Figure 4 This is the SEM image of the microcrystalline glass in Example 1 of the present invention.

[0046] Terminology Certain embodiments of the present invention are now described in detail, examples of which are illustrated by the accompanying structural formulas and chemical formulae. The present invention is intended to encompass all substitutions, modifications, and equivalent technical solutions, which are all included within the scope of the invention as defined in the claims. Those skilled in the art will recognize that many methods and materials similar or equivalent to those described herein can be used to practice the present invention. The present invention is in no way limited to the methods and materials described herein. In the event that one or more of the combined documents, patents, and similar materials differ from or contradict the present application (including but not limited to defined terms, term applications, described technologies, etc.), the present application shall prevail.

[0047] It will be further appreciated that certain features of the invention, which, for clarity, are described in the context of separate embodiments, may also be provided in combination in a single embodiment. Conversely, various features of the invention, which, for brevity, are described in the context of a single embodiment, may also be provided separately or in any suitable subcombination.

[0048] Unless otherwise specified, all technical terms used in the present invention have the same meaning as commonly understood by those skilled in the art to which the present invention belongs. All patents and publications related to the present invention are incorporated herein by reference in their entirety.

[0049] In the description of this specification, the reference terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" mean that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art can combine and combine different embodiments or examples described in this specification and features of different embodiments or examples without contradiction.

[0050] In the following description, all numbers disclosed herein are approximate, regardless of whether the word "about" or "approximately" is used. The numerical value of each number may vary by 1%, 2%, 5%, 7%, 8%, 10%, 15%, or 20%. Whenever a number having a value of N is disclosed, any number having a value of N+ / -1%, N+ / -2%, N+ / -3%, N+ / -5%, N+ / -7%, N+ / -8%, N+ / -10%, N+ / -15%, or N+ / -20% is expressly disclosed, where "+ / -" means plus or minus.

[0051] Base glass: Glass that has not been nucleated, crystallized, or strengthened Glass-ceramics: A type of solid composite material that contains both glass phase and crystal phase (microcrystalline phase, crystalline phase, and crystalline phase) and is prepared by targeted and controlled crystallization of substrate glass.

[0052] Glassy phase: An amorphous mineral phase with low refractoriness. It is glassy at room temperature and gradually softens during heating, eventually becoming a liquid. The glassy phase, alone or in combination with some crystalline minerals, fills the gaps between the main crystalline phases to form the material matrix. It is also called the binding phase or amorphous phase.

[0053] The crystalline phase, including the primary crystalline phase and the secondary crystalline phase, is the microscopic structure of the crystal and is a general term for the parts composed of a large number of crystalline solid phases.

[0054] Chemically strengthened glass-ceramics are solid composite materials obtained by chemically strengthening glass-ceramics samples. During high-temperature chemical strengthening, alkali metal ions with larger ionic radii (such as potassium and sodium ions) in the salt bath / molten salt replace alkali metal ions with smaller ionic radii (such as sodium and lithium ions) in the glass sample. This creates a size difference in the exchanged ions and generates compressive stress on the glass surface. Glass samples include, but are not limited to, substrate glass (without a crystalline phase) and glass-ceramics.

[0055] Nucleation: Through heat treatment, the nucleating material in the glass grows small crystal nuclei.

[0056] Crystallization: growing a certain crystal based on a crystal nucleus through heat treatment.

[0057] Crystallinity R: the percentage of total crystalline mass to the total mass of glass-ceramics b-value: This is the b-value in the color space (LAB) and represents the yellow-blue value of a material. In this invention, b-value refers to the b-value for transmitted light. A positive b-value indicates a bluish tint. b-values ​​were measured using a Konica Minolta CM-3600D spectrophotometer.

[0058] Transmittance (Tr) refers to the ratio of the radiant energy that is projected and transmitted through an object to the total radiant energy that is projected onto the object, during the process from the incident light flux (i.e., the incident surface or the incident surface of a medium) to the incident light flux (i.e., the incident light flux) to the other side. In the Examples and Comparative Examples of the present invention, the transmittance of glass-ceramics at a wavelength of 550nm refers to the average transmittance of multiple glass samples from the same batch measured at 550nm. At least five glass-ceramics samples from each batch were measured.

[0059] Haze: Characterizes the cloudy state caused by light scattering inside or on the surface of a transparent or translucent sample, that is, the ratio of scattered transmitted light to total transmitted light, which is determined by the scattered light flux, and the percentage of transmitted light intensity that deviates from the incident light by more than 2.5° to the total transmitted light intensity.

[0060] DOL_0: Depth of the compressive stress layer, also known as the compressive stress depth, is the distance from any surface of the glass-ceramic to the point close to that surface where the compressive stress is zero. It is measured using the SLP-2000 stress meter. The unit is μm. The refractive index of the refractive fluid used in the SLP-2000 is 1.51.

[0061] DOL_K: Depth of K ion exchange layer, also known as K+ ion compressive stress depth.

[0062] CT_LD (Tensile Stress Line Density): The ratio of the tensile stress integral to the thickness of a glass-ceramic, as measured by the SLP stress instrument, is obtained. Compressive and tensile stresses in chemically strengthened glass-ceramics are in equilibrium, and the SLP2000 stress meter provides more accurate measurements of the tensile stress region of glass-ceramics. Therefore, the ratio of the tensile stress integral to the thickness is used to represent the stress per unit thickness of the glass-ceramic and to characterize the stress level of chemically strengthened glass-ceramics.

[0063] CT_CV: refers to the maximum value of all tensile stresses in the tensile stress zone Surface compressive stress: Surface compressive stress (CS) is determined by chemical strengthening of glass-ceramics, where smaller alkali metal ions are replaced by larger alkali metal ions. This crowding effect of these larger alkali metal ions generates compressive stress on the glass surface, known as surface compressive stress. CS30 is the compressive stress at a strengthening depth of 30 μm. Surface CS is measured using an SLP 2000 stress meter and is expressed in MPa. DETAILED DESCRIPTION

[0064] To make the objectives, technical solutions, and advantages of the present invention more clearly understood, the present invention will be further described in detail below with reference to the following examples. The specific embodiments described herein are intended only to illustrate the present invention and are not intended to limit the present invention in any way. In addition, in the following description, descriptions of known structures and technologies are omitted to avoid unnecessary confusion about the concepts of the present disclosure. Such structures and technologies are also described in many publications.

[0065] The reagents used in the present invention can be purchased from the market or prepared by the method described in the present invention.

[0066] In this embodiment, SiO2 and Al2O3 are the main network oxides and intermediate oxides of the base glass and microcrystalline glass. The two mainly form the glass network. Maintaining them within a certain range in the glass phase can effectively ensure that the network structure inside the microcrystalline glass is larger. In order to ensure efficient ion exchange and strengthening effects, the present invention restricts the content of the two in the residual glass phase.

[0067] SiO2, as one of the main components of the network oxide of basic glass and microcrystalline glass, is one of the important components of Si-O tetrahedron in the main body and the network structure. Based on the raw materials involved in the embodiment of the present invention, the mass fraction of SiO2 is 40.0-62.0%, preferably 45.0-60.0%, for example, it can take values ​​of 40.0%, 42.0%, 43.0%, 44.0%, 45.0%, 46.0%, 47.0%, 48.0%, 49.0%, 50.0%, 51.0%, 52.0%, 53.0%, 54.0%, 55.0%, 58%, 62% and any two of the above values ​​constitute any component in the range.

[0068] Al2O3 is the intermediate oxide formed by glass, is also the main component of the crystal formations such as sodium pyroxene, triclinic pyroxene, eucryptite, can significantly improve the thermal stability of basic glass and glass-ceramics, simultaneously because [AlO4] is larger than [SiO4] volume, can provide larger space for ion exchange, therefore, aluminum oxide can promote the carrying out of ion exchange. Too high Al2O3 can increase the viscosity of glass, is unfavorable for melting. Based on the raw material related to the embodiment of the present invention, Al2O3 mass fraction is 15.0-26.0%, preferably 15.0-19.0%, for example, can take the value of 15.0%, 16.0%, 17.0%, 18.0%, 19.0%, 20.0%, 21.0%, 22.0%, 23.0%, 24.0%, 25.0%, 26.0% and any one numerical value in any two of the above-mentioned number components constituting the composition range.

[0069] The three alkali metal oxides, Na2O, Li2O, and K2O, are external oxides in the base glass network. They can effectively ensure the degree of bond breaking of the bridging oxygen bonds within the base glass, breaking up the original base glass network structure, reducing the glass viscosity and melting difficulty. During the heat treatment of the base glass, it is beneficial to promote the crystallization of the base glass.

[0070] Na2O is one of the main components of crystal forms such as sodium pyroxene and triclinic pyroxene, and is also an important element in the subsequent chemical strengthening process. At the same time, Na2O is a flux when the base glass is melted at high temperature, which can significantly reduce the melting temperature of the base glass. However, when the Na2O content is too high, the chemical stability of the microcrystalline glass is significantly reduced. Therefore, the ideal Na2O mass fraction is 8.0%-16.0%. At this time, it can not only keep the melting temperature within a suitable range, but also ensure that the Na2O in the residual glass phase in the microcrystalline glass is controlled within a reasonable range. In this way, the external oxides of the microcrystalline glass network can be kept within a reasonable range, so that the microcrystalline glass has good ion exchange properties. The mass fraction of Na2O in the present invention is in the range of 8-12%, specifically 8.0%, 9.0%, 10.0%, 11.0%, 12.0%, 13.0%, 14.0%, 15.0%, 16.0% and a value in one or two composition ranges among the above values.

[0071] K2O can reduce the high-temperature viscosity of the base glass, significantly improve the formability and fluidity of the base glass at high temperatures, and significantly reduce the incidence of cracks. Among them, a small amount of K2O can not only slow down the crystallization behavior during the molding of micro-ceramic glass, but also promote the formation of sodium pyroxene, triclinic pyroxene or sodium silicate crystals during the crystallization process. When the mass content of K2O exceeds 2.0%, crystalline phases such as potassium feldspar will be generated, which will harm its mechanical strength and optical properties. At the same time, the addition of an appropriate amount of K2O is beneficial to K + and Na + The exchange of ions enhances the strengthening effect. The mass percentage of K2O in the base glass involved in the embodiments of the present invention is in the range of 0.1-3.00%, preferably 0.5-3% or 0.2-2%. Specifically, in the present invention, it can be any value in the range of 0.2%, 0.4%, 0.6%, 0.8%, 1.0%, 1.2%, 1.4%, 1.6%, 1.8%, 2.0%, or any value in the range consisting of any two of the above values.

[0072] Li2O is an oxide with high alkali metal activity and is an external oxide of the glass network. As one of the additives to reduce the high temperature viscosity of the base glass, it can significantly improve the high temperature fluidity of the base glass. + In the microcrystalline glass provided by the present invention, the constituent elements of eucryptite can also participate in the ion exchange chemical strengthening reaction to further enhance the mechanical properties of the microcrystalline glass. Strictly controlling its content can effectively control the proportion of eucryptite in the microcrystalline glass described in the present invention. The mass proportion content range of Li2O involved in the embodiments of the present invention is 2-10.0%, which can be 2.0%, 3.0%, 4.0%, 6.0%, 8.0%, 9.0%, 10.0% and any value in the range composed of any two of the above values.

[0073] P2O5 can be used as a nucleating agent in base glass and glass-ceramics, promoting phase separation and overall crystallization in the base glass. If the P2O5 concentration is too low, the base glass will not easily crystallize, and crystals will only form from the surface inward at higher temperatures and lower viscosities. If the P2O5 concentration is too high, cooling during the base glass formation process will be difficult to control and may lead to devitrification. In the embodiments of the present invention, the P2O5 content by weight ranges from 2.50% to 6.00%, and specifically can be any value within a range consisting of 2.5%, 3.0%, 3.5%, 4.0%, 5.0%, 6.0%, or any other value within a range consisting of any two of the aforementioned values.

[0074] ZrO2 is an intermediate oxide in glass formation, which can improve the chemical stability of glass, increase its hardness, and enhance its resistance to scratches and drops. At the same time, due to its high cationic charge and strong electric field, ZrO2 has a significant accumulation effect on the glass structure and is commonly used as a nucleating agent in microcrystalline glass. However, excessive ZrO2 can significantly increase the viscosity of the glass and affect its forming ability. In the embodiments of the present invention, the mass percentage of ZrO2 ranges from 0.5-3%, preferably from 1.0-3.0%, and specifically can be 0.5%, 1.0%, 1.5%, 2.0%, 2.5%, 3.0%, or any other value within a range consisting of any two of the aforementioned values.

[0075] B2O3, as a network exosome oxide of glass, is generally filled in the voids of the silicon-oxygen tetrahedral skeleton. Its cation coordination rarely changes, and some properties of its oxide can be considered constant. B2O3 helps to provide a base glass with a low melting temperature. In addition, adding B2O3 to the base glass can also improve the damage resistance of the microcrystalline glass. The raw materials involved in the embodiments of the present invention have a B2O3 content range of 0.5-6.00%. Specifically, in the present invention, it can be 0.5%, 1.0%, 1.5%, 2.0%, 2.5%, 3.0%, 3.5%, 4%, 5%, 6% and any value in the range composed of any two of the above values.

[0076] Y2O3 stabilizes ZrO2 and improves the strength and elastic modulus of glass. Excessive Y2O3 additions can increase the tendency of base glass to crystallize. Its mass percentage range is 0.1-1%. Specifically, Y2O3 can be 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, or any value within a range consisting of any two of these values.

[0077] In some embodiments, the microcrystalline glass also includes a refractive index adjuster, which is selected from one of the following: La2O3 0.1-10%; and or CeO2: 0.1-3%; and or, Nb2O5: 0.1-3%; and or, TiO2: 0.1-5%; and or, HfO2: 0.1-5%, and or, BaO: 2-8%, and the refractive index improvement coefficient k of La2O3, CeO2, Nb2O5, TiO2, HfO2, and BaO in the residual glass phase of the microcrystalline glass satisfies: 0.05≤k≤0.2, k = (0.015×[La2O3] + 0.02×[CeO2]+ 0.012×[Nb2O5]+ 0.02×[TiO2]+ 0.012×[HfO2]+ 0.012×[BaO]).

[0078] These oxide components mainly exist in the glass phase as glass network modifications, have high field strength, and can adjust the refractive index of the glass phase, making it closer to the crystal phase, reducing the scattering of the microcrystalline glass and reducing the haze.

[0079] In some embodiments, in the refractive index modifier, the mass proportion of La2O3 can be 0, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 9%, 10%, and any value in the range consisting of any two of the above values; the mass proportion of CeO2 can be 0, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 2%, 2.5%, 3%, and any value in the range consisting of any two of the above values; the mass proportion of Nb2O5 can be 0, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 2%, 2.5%, 3%, and any value in the range consisting of any two of the above values. any value in the range consisting of any two of the above numerical values; the mass proportion of TiO2 can be 0, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, and any value in the range consisting of any two of the above numerical values; the mass proportion of HfO2 can be 0, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, and any value in the range consisting of any two of the above numerical values; the mass proportion of BaO can be 1%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, and any value in the range consisting of any two of the above numerical values.

[0080] The basic glass component content involved in the present invention also includes a clarifier with a mass percentage of 0.10-1.0%, which can effectively homogenize and clarify the basic glass components and eliminate bubbles inside the glass. The clarifier is selected from one or more of SnO2, SnO, NaCl, Na2SO4, Sb2O3, As2O3, nitrate, and sulfate; the mass percentage of SnO2 can be 0, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1% and any value in the range of any two of the above values; the mass percentage of SnO can be 0, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1% and any value in the range of any two of the above values. the mass proportion of NaCl can be specifically 0, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1% and any value in the range consisting of any two of the above values; the mass proportion of Na2SO4 can be specifically 0, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1% and any value in the range consisting of any two of the above values; the mass proportion of the clarifier component can be 0.10%, 0.20%, 0.30%, 0.40%, 0.50%, 0.60%, 0.70%, 0.80%, 0.90%, 1.0% and any value in the range consisting of any two of the above values.

[0081] The matrix glass, glass-ceramics and glass-ceramics products of the present invention can be produced and manufactured by the following methods: S1. uniformly mixing the chemical components for preparing the glass-ceramics, and melting them at a temperature of 1450-1650° C. to obtain a glass melt; S2, clarifying and homogenizing the molten liquid at a temperature of 1450-1550° C., and forming and annealing the molten liquid to obtain a base glass; S3. Heat-treating the base glass to obtain the transparent glass-ceramics.

[0082] In some embodiments, the melting temperature is 1450°C, 1500°C, 1550°C, 1600°C, 1650°C, or any one of the ranges formed by any two of the above values.

[0083] In some embodiments, the clarification and homogenization temperature is 1450°C, 1460°C, 1470°C, 1480°C, 1490°C, 1500°C, 1550°C, or any one in a range consisting of any two of the above values.

[0084] In some embodiments, the annealing temperature is 450-500° C. and is maintained for 4-8 hours. Preferably, the annealing temperature is 450° C., 460° C., 470° C., 480° C., 490° C., 500° C., or any one in a range consisting of any two of the above values. Preferably, the holding time is 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, or any one in a range consisting of any two of the above values.

[0085] The base glass made from S2 undergoes a single-stage crystallization process (heat treatment), allowing for continuous nucleation and crystal growth. Specifically, the temperature is raised to a specified nucleation and crystallization temperature. After reaching the nucleation temperature, the temperature is maintained for a specified period before the temperature is raised again for crystallization. The heat treatment process is as follows: first, the temperature is raised to a nucleation temperature of 500-550°C and held for 1-5 hours. Then, the temperature is raised to 600-800°C for crystallization and held for 1-3 hours. This staged heat treatment process yields glass-ceramics with uniform grain size. Preferably, the nucleation temperature is 500°C, 510°C, 520°C, 530°C, 540°C, 550°C, or any other range consisting of any two of these values. Preferably, the hold time is 1 hour, 2 hours, 3 hours, 4 hours, 5 hours, or any other range consisting of any two of these values. Preferably, the crystallization treatment temperature is 600°C, 610°C, 620°C, 630°C, 640°C, 650°C, 660°C, 670°C, 680°C, 700°C, 710°C, 720°C, 730°C, 750°C, 800°C, or any one in a range consisting of any two of the above values. Preferably, the holding time is 1 hour, 1.5 hours, 2 hours, 2.5 hours, 3 hours, or any one in a range consisting of any two of the above values.

[0086] In some embodiments, chemically strengthened glass-ceramics are obtained by chemical strengthening.

[0087] In some embodiments, the matrix glass or glass-ceramic can be ion-exchanged by immersing it in a salt bath of molten sodium salt (such as NaNO3) at a temperature of about 350-480°C for about 1-36 hours, preferably in the temperature range of 400-480°C, and preferably in the time range of 2-15 hours. In some embodiments, Na ions replace some of the Li ions in the matrix glass or glass-ceramic, thereby forming a surface compressive stress layer and exhibiting high mechanical properties. Preferably, the temperature is 350°C, 360°C, 370°C, 380°C, 400°C, 410°C, 420°C, 430°C, 440°C, 450°C, 460°C, 470°C, 480°C, and any one of the ranges formed by any two of the above values. Preferably, the time is 1 hour, 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, 10 hours, 12 hours, 14 hours, 15 hours, 20 hours, 25 hours, 30 hours, 35 hours, 36 hours, and any one in the range formed by any two of the above values.

[0088] In some embodiments, the matrix glass or glass-ceramics can be ion exchanged by immersing in a mixed salt bath of molten potassium salt (such as KNO3) and sodium salt (such as NaNO3) at a temperature of about 360-480°C for 1-36 hours, preferably in the range of 0.5 to 24 hours. Preferably, the temperature is 350°C, 360°C, 370°C, 380°C, 400°C, 410°C, 420°C, 430°C, 440°C, 450°C, 470°C, 480°C, and any ranges consisting of any two of the above values. Preferably, the time is 0.5 hour, 1 hour, 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, 10 hours, 12 hours, 14 hours, 15 hours, 20 hours, 24 hours, 25 hours, 30 hours, 35 hours, 36 hours, and any ranges consisting of any two of the above values. Preferably, in the mixed salt, the ratio of potassium salt to sodium salt is 3:7, 1:1, 2:3, 1:4, 3:2, 4:1, 7:3 and any one in the range formed by any two of the above values.

[0089] The glass-ceramics disclosed herein exhibit efficient low-temperature ion exchange performance. In some embodiments, at relatively low ion exchange temperatures and short exchange times, the depth of the Na ion exchange layer can reach over 110 μm. After ion exchange, the hardness of the glass-ceramics is significantly improved. This is primarily due to the "crowding effect" of ion exchange, which creates high compressive stress on the surface of the glass-ceramics, enhancing their deformation resistance and hardness.

[0090] In some embodiments, after chemical strengthening, the glass-ceramics of the present invention can obtain a glass-ceramics product having a Vickers hardness of up to 700 kgf / mm. 2 above.

[0091] After repeated experiments and studies, the inventors of the present invention obtained the transparent microcrystalline glass or transparent microcrystalline glass products of the present invention by specifying the content and content ratio of the specific components constituting transparent microcrystalline glass and transparent microcrystalline glass products to specific values ​​and making them contain specific crystal phases.

[0092] Glass-ceramic performance index test: 1. Optical Performance Testing: Glass-ceramics were tested for b-value, transmittance, and haze using professional testing equipment according to GB / T 7962.12-2010, Test Methods for Colorless Optical Glass - Part 12: Spectral Transmittance. The instrument used in this article is a Konica Minolta CM-3600D spectrophotometer.

[0093] 2. XRD test: The crystallized glass-ceramics was ground into a fine glass powder with a particle size of less than 75 μm. The powder was then tested using an X-ray diffractometer to obtain an XRD diffraction peak curve. The XRD diffraction data was then analyzed using professional software to obtain data such as crystallinity and average grain size. The X-ray diffractometer used in the present invention was a Rigaku D / max3B, with a copper target. The diffraction angle range used in the test was 2θ = 10 to 80°, a scanning speed of 0.2 to 6° / min, an operating voltage of 40 kV, and an operating current of 30 mA.

[0094] 3. Crystal content / crystallinity test method: Import the X-ray diffractometer test result file (RAW format) into the X-ray diffraction data Rietveld refinement software (such as Gsas, Fullprof, Maud) for fitting and calculation. The ratio of the fitted crystalline phase peak area to the fitted total peak area is the crystal content / crystallinity.

[0095] 4. Average grain size: The glass-ceramic sample was tested using an X-ray diffractometer. The average grain size was obtained by applying the Scherrer formula D=Kλ / (βcosθ) to the XRD test data, where λ is the X-ray wavelength of 0.154056 nm, β is the peak half-height width, and K=0.89.

[0096] 5. Differential Scanning Calorimetry (DSC) Testing: The testing instrument was a NETZSCH STA449F3 thermogravimetric and simultaneous thermal analyzer. The sample was ground and passed through a 200-mesh sieve. The testing conditions were room temperature to 1100°C, with a heating rate of 10°C / min.

[0097] 6. Three-point bending: In order to test the strength of the dental glass-ceramics, the glass-ceramics were cut into 10 rectangular blocks of about 50 mm in length, 5 mm in width and 4 mm in height. The rectangular blocks were then ground and polished to obtain long strips of glass-ceramics. A universal testing machine was used to perform a three-point bending strength test on the long strips of glass-ceramics to calculate their average bending strength. The instrument loading speed was 1 mm / min, and the lower span was 20 mm. The maximum load could be obtained when the glass was broken. The following formula (I) can be used to calculate the fracture strength of the sample. Formula (I) is: M=(3W l ) / (2bd 2 ); where M is the three-point bending strength (MPa), W is the maximum load (N), l is the span (mm), b is the sample width (mm), and d is the sample thickness (mm). The breaking strength of the sample can be obtained by calculation.

[0098] 7. Microhardness test: Use HV-50 Vickers hardness tester to test the hardness of the material, with a load of 1kg and a loading time of 10ms. To make the sample into a standard specimen, the material surface needs to be polished to a mirror finish, ensuring that the upper and lower surfaces are parallel. Test 10-15 points on each sample and then take the average value. Calculate using formula (II): HV = 1.8444 × (P / d 2 ) where P is the test load in N and d is the average length of the diagonal of the indentation in mm.

[0099] 8. Drop ball impact test A sample of a microcrystalline glass product of 145mm×67mm×0.7mm is placed on a glass supporting fixture, and a 132g steel ball is dropped from a specified height, with the landing point being the center point of the sample. This is the maximum drop ball test height at which the sample can withstand the impact without breaking. Specifically, the drop ball test height starts at 400mm, and the ball is dropped once at each height. If the sample does not break, the test is continued by successively rising 100mm until the sample breaks. For the embodiments with a "drop ball test height", microcrystalline glass products are used as test objects. The test data recorded as 1700mm in the embodiment indicates that the microcrystalline glass product can withstand the impact without breaking even if a steel ball is dropped from a height of 1700mm. The gravitational potential energy of the drop ball test height in the present invention is the drop ball impact energy.

[0100] 9. Drop test: The drop resistance test was carried out using a directional drop tester WH-2101. By loading glass products of the same specifications on 2D glass-ceramic products (each weighing 20g, with 2 pieces loaded), laying 60-80 mesh sandpaper on the base, and letting it fall freely from a specified height, the sample hits the sandpaper directly, and the height at which it can withstand the impact without breaking is the drop resistance. Specifically, the test is carried out from a height of 600mm. Without breaking, the height is changed in sequence through 700mm, 800mm, 900mm, 1000mm and above. For the embodiments with "drop resistance", glass-ceramic products are used as test objects. The test data recorded as 1000mm in the embodiment indicates that even if the glass-ceramic product with a load is dropped from a height of 1000mm, it will withstand the impact without breaking. The maximum experimental height of the drop tester WH-2101 is 2000mm.

[0101] Example The preparation process of the transparent glass-ceramics of Examples 1-7 is as follows: S1. The components in Table 1 are uniformly mixed in an alumina crucible, melted at a temperature of 1450-1650° C., and kept warm for 4-10 hours to obtain a glass melt; S2, clarifying and homogenizing the molten liquid at a temperature of 1450-1550° C., casting and forming, and annealing at 450-500° C. for 4-8 hours to obtain a basic glass; S3. Put the base glass into a muffle furnace, first heat it to a nucleation treatment temperature of 500-550° C. and keep it warm for 1-5 hours, then heat it to 600-800° C. for crystallization treatment and keep it warm for 1-3 hours to obtain the transparent microcrystalline glass.

[0102] S4. Immerse the obtained transparent microcrystalline glass in a salt bath of molten NaNO3 at 350-480°C for about 1-36 hours to perform ion exchange, thereby obtaining a microcrystalline glass product.

[0103] The specific temperature and time during the preparation process are shown in Table 2.

[0104] Table 1 Components of the Examples

[0105] Table 2 Preparation process condition screening

[0106] The transparent glass-ceramics prepared in Examples 1-7 were subjected to performance tests according to the method described in the section "Testing the Performance of Glass-ceramics" of the present invention. The test results are shown in Table 3: Table 3 Effect data of Examples 1-7

[0107] It can be seen from the data in Tables 1 to 3 that the present invention strictly controls the crystalline phase ratio of the main crystalline phase and the glass phase in the transparent microcrystalline glass by regulating the ratio and proportion of the components and adjusting the preparation process, thereby controlling the average grain size of the transparent microcrystalline glass (≤50 nm) and reducing the light scattering performance (such as transparency, haze (≤0.1%), transmittance (when the thickness of the microcrystalline glass is ≤2.0 mm, at a visible light wavelength of 550 nm, Tr ≥89%), etc.).

[0108] The grain size of Examples 1-7 of the present invention is 18-35 nm, the total crystallinity R is 42-70%, the transmittance is ≥89.7%, and the haze is between 0.06-0.09; while having good mechanical properties and drop resistance, the transmittance, anti-light scattering performance, etc. are effectively improved.

[0109] from Figure 3 It can be seen that the main crystals in the transparent microcrystalline glass obtained in Example 1 and Example 2 include sodalite and eucryptite, indicating that the transparent microcrystalline glass prepared by the present invention contains sodalite and eucryptite as main crystals.

[0110] from Figure 4 It can be seen that the crystal grain size of the microcrystalline glass obtained in Example 1 is controlled to be below 50 nm, and the microcrystalline glass can reduce the light scattering performance.

[0111] Comparative Example The difference from Example 1 is that the chemical components of each comparative example are prepared according to the settings in Table 4, and the rest of the preparation process is consistent with Example 1.

[0112] Table 4 Comparative Example Setting Components

[0113] The transparent glass-ceramics prepared in Comparative Examples 1-5 were subjected to performance tests according to the method described in the section "Test of Performance Index of Glass-Ceramics" of the present invention. The test results are shown in Table 5: Table 5 Effect data of each component of comparative example

[0114] From the results in Tables 1 to 5, we can see that (1) The k value in Comparative Example 1 is not controlled within a reasonable range, and the haze H, |b|, and |Δn| of the obtained transparent microcrystalline glass are significantly greater than the effect data of the transparent microcrystalline glass obtained in Examples 1-7 of the present invention. It can be seen that Examples 1-7 of the present application effectively eliminate the phase interface but do not eliminate the scattering loss caused by Fresnel reflection at the phase interface.

[0115] (2) The crystalline phase ratio of the main crystalline phase to the glass phase in Comparative Example 2 does not meet the requirements of the relationship between M, N, and L. The haze H, |b|, and |Δn| of the resulting transparent glass-ceramics are significantly greater than the performance data of the transparent glass-ceramics obtained in Examples 1-7 of the present invention. Based on the performance data, although the nanocrystals in Comparative Example 2 are close to 50 nm, the haze H, |b|, and |Δn| still do not meet the relevant requirements.

[0116] (3) Comparative Example 3 lacks a refractive index regulator, and the haze H, |b|, and |Δn| of the obtained transparent microcrystalline glass do not meet the requirements, and the scattering loss caused by Fresnel reflection at the phase interface cannot be eliminated; the Vickers hardness and Young's modulus are both relatively small. In the effect data of the transparent microcrystalline glass obtained in Examples 1-7 of the present invention, by introducing a refractive index regulator and proposing a refractive index improvement coefficient (satisfying 0.05≤k≤0.2), the refractive index difference between the crystal phase (primary crystal phase and secondary crystal phase) and the glass phase is reduced (the maximum refractive index difference between the glass phase and the crystal phase at a wavelength of 587.6nm |Δn|≤0.04, and the color control color coordinate b value range is: |b|≤1.5.), eliminating the scattering loss caused by Fresnel reflection at the phase interface, and improving the light scattering problem caused by the large refractive index of some crystal phases with high refractive index and high elastic modulus and the glass phase. Combined Figure 1 and Figure 2 By comparing the results, it can be clearly seen that the transparent microcrystalline glass prepared in Example 1 of the present invention has improved haze and reduced light scattering performance.

[0117] (4) Comparative Example 4 lacks a clarifier, which prevents homogenization of the clarified glass components and the elimination of bubbles within the glass. Compared to the performance data of the transparent glass-ceramics obtained in Inventive Examples 1-7, the haze H, |b|, and |Δn| of the transparent glass-ceramics obtained in Comparative Example 4 are all larger.

[0118] (5) Comparative Example 5 lacks a clarifier and a refractive index regulator, and the main crystal phase and the residual glass phase in the prepared transparent microcrystalline glass cannot satisfy the relevant formula for the relationship between M, L, and N. From the effect data, the haze H, |b|, and |Δn| of the transparent microcrystalline glass obtained in Comparative Example 5 are all large, and the Vickers hardness and Young's modulus are both small.

[0119] In summary, the transparent glass-ceramics obtained in Examples 1-7 of the present invention can effectively solve the problem of severe light scattering of polycrystalline high-strength glass-ceramics and the problem of high haze caused by the difference between the interface of the crystalline phase and the amorphous phase by controlling the proportion of sodium cryptite and eucryptite in the main crystal, the proportion of the residual glass phase, the total crystallinity R, the refractive index modifier, the introduction of the glass phase refractive index improvement coefficient k, the proportion of the clarifier, and other factors. From the comparison of Examples 1-7 and Comparative Examples 1-5, it can be seen that the transparent glass-ceramics prepared by the present invention reduces its haze and improves its optical clarity while maintaining the high strength of the glass-ceramics.

[0120] The methods of the present invention have been described through preferred embodiments. It is apparent that those skilled in the art will be able to modify or appropriately alter and combine the methods and applications described herein within the scope, spirit, and spirit of the present invention to implement and apply the technology of the present invention. Those skilled in the art may refer to the disclosure herein and appropriately modify the process parameters to achieve the desired effect. It is particularly important to note that all similar substitutions and modifications apparent to those skilled in the art are considered encompassed by the present invention.

Claims

1. A transparent glass-ceramic, characterized in that: The transparent microcrystalline glass comprises a main crystalline phase, a secondary crystalline phase and a residual glass phase; The main crystalline phase includes sodium cryptite and eucryptite, The secondary crystalline phase includes at least one of zirconium oxide and beta quartz solid solution; The total crystallinity R is 40wt%-75wt%, In the transparent glass-ceramics, the residual glass phase accounts for M, the sodium nephrite accounts for N, and the eucryptite accounts for L, calculated by mass percentage. The following relationship must be satisfied among M, L, and N in the glass-ceramics: 1) 1.520≤(M×1.51+N×1.54+L×1.60)≤1.550; 2) 2.35≤N / L≤19.

0.

2. The transparent glass-ceramics according to claim 1, characterized in that: The total crystallinity R of the transparent glass-ceramics is 50-65wt%; and / or, an N / L value of 4-17.

3. The transparent glass-ceramics according to claim 1, characterized in that: The chemical components of the transparent microcrystalline glass, calculated by mass percentage, include: SiO2: 40-62%, Al2O3: 15-26%, Na2O: 8-16%, K2O: 0.1-3%, Li2O: 2-10%, B2O3: 0.5-6%, P2O5: 2.5%-6.0%, ZrO2: 0.5-3.0%, Y2O3: 0.1-3% and clarifier: 0.1-1%.

4. The transparent glass-ceramics according to any one of claims 1 to 3, characterized in that: The chemical components of the glass-ceramics include a refractive index modifier; And / or, the refractive index adjuster is at least one of La2O3, CeO2, Nb2O5, TiO2, HfO2, and BaO.

5. The transparent glass-ceramics according to claim 4, characterized in that: In terms of mass percentage, the refractive index modifier is selected from at least one of the following components: La2O3: 0-10%, CeO2: 0-3%, Nb2O5: 0-3%, TiO2: 0-5%, HfO2: 0-5%, and BaO: 1-8%.

6. The transparent glass-ceramics according to any one of claims 4 or 5, characterized in that: La2O3, CeO2, Nb2O5, TiO2, HfO2, and BaO in the glass phase make the glass phase refractive index improvement coefficient k satisfy: k=(0.015×[La2O3]+0.02×[CeO2]+0.012×[Nb2O5]+0.02×[TiO2]+0.012×[HfO2]+0.012×[BaO]), satisfying 0.05≤k≤0.

20.

7. The transparent glass-ceramics according to claim 3, characterized in that: The clarifier is at least one of SnO2, SnO, NaCl, and Na2SO4; And / or, the clarifier accounts for 0.10-1.0% in the glass-ceramics; And / or, the clarifier is selected from at least one of the following components: SnO2: 0-1.0%, SnO: 0-1.0%, NaCl: 0-1.0%, Na2SO4: 0-1.0%.

8. A method for preparing the transparent glass-ceramics according to any one of claims 1 to 7, characterized in that: The steps include: S1. uniformly mixing the chemical components and melting them at a temperature of 1450-1650° C. to obtain a glass melt; S2, clarifying and homogenizing the molten liquid at a temperature of 1450-1550° C., and obtaining a base glass after forming and annealing; S3. Heat-treating the base glass to obtain the transparent glass-ceramics.

9. The preparation method according to claim 8, characterized in that: The forming method includes one of the float method, rolling method, overflow down-draw method and continuous melting casting method; The heat treatment process of the base glass is as follows: firstly, the temperature is raised to 500-550°C for nucleation treatment and kept at this temperature for 1-5 hours, then the temperature is raised to 600-800°C for crystallization treatment and kept at this temperature for 1-3 hours; And / or, the annealing temperature is 450-500° C. and maintained for 4-8 hours; And / or, the transparent glass-ceramics or base glass is chemically strengthened to obtain chemically strengthened glass-ceramics; And / or, the chemical strengthening process is selected from one of the following methods: (1) the transparent micro-ceramic or base glass is subjected to ion exchange by immersing in a salt bath of molten sodium salt at a temperature of about 350-480°C for 1-36 hours, (2) the matrix glass or micro-ceramic is subjected to ion exchange by immersing in a mixed salt bath of molten potassium salt and sodium salt at a temperature of about 360-480°C for 0.5-36 hours.

10. Use of the transparent microcrystalline glass according to any one of claims 1 to 7 or the transparent microcrystalline glass prepared by the method according to any one of claims 8 to 9 as a protective cover material for electronic consumer products or a protective cover material for vehicle-mounted display devices.

Citation Information

Patent Citations

  • Glass ceramic and preparation method thereof

    CN115893851A

  • Glass ceramic, glass ceramic product and manufacturing method thereof

    CN120271235A